2014
DOI: 10.1111/jsm.12668
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the Androgen Receptor Gene and Hormonal Contraceptive Induced Provoked Vestibulodynia

Abstract: Aim Women who developed vestibulodynia (vulvar vestibulitis) while taking combined hormonal contraceptives (CHCs) and a control group of women were tested for polymorphisms of the gene coding for the androgen receptor (AR) that is located on the X chromosome. Study Design DNA from 30 women who developed vestibulodynia while taking CHCs and 17 control women were tested for the number of cytosine–adenine–guanine (CAG) trinucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 32 publications
(37 reference statements)
0
41
0
4
Order By: Relevance
“…Working with physical therapists, Reissing et al [50] found that women with vaginismus demonstrated significantly higher vaginal/pelvic muscle tone and lower muscle strength than women with PVD or controls. Single Bcandidate^gene research has been performed in the field of vulvodynia, and genetic polymorphisms have been linked to the development of vulvar pain [51][52][53][54][55][56]. Although to date, there is evidence for heritability in other chronic pain syndromes [57], no heritability studies have been performed in the context of vulvodynia.…”
Section: Biomedical Factorsmentioning
confidence: 99%
“…Working with physical therapists, Reissing et al [50] found that women with vaginismus demonstrated significantly higher vaginal/pelvic muscle tone and lower muscle strength than women with PVD or controls. Single Bcandidate^gene research has been performed in the field of vulvodynia, and genetic polymorphisms have been linked to the development of vulvar pain [51][52][53][54][55][56]. Although to date, there is evidence for heritability in other chronic pain syndromes [57], no heritability studies have been performed in the context of vulvodynia.…”
Section: Biomedical Factorsmentioning
confidence: 99%
“…Goldstein et al . 69 identified a genetic polymorphism in the AR in PVD patients and concluded that an inefficient AR combined with lowered free testosterone predisposes to PVD. This has not been confirmed.…”
Section: Hormonal Factorsmentioning
confidence: 99%
“…On the other hand, the local absorption of estrogen may influence the urinary environment exerting a protective action very similar to that observed in postmenopausal women [11]. Burrows and Goldstein have recently proposed the use of topical estradiol 0.03% and testosterone 0.01% to the vestibule twice daily in order to treat vestibulodynia in premenopausal women assuming CHC [31], a side-effect probably derived by a genetic disposition to have inefficient androgen receptor [32]. Interestingly enough, in our study sample, the rate of current or previous use of CHC is quite high suggesting the potential involvement of estro-progestin preparations in the pathophysiology of IC/PBS and/or the clinical expression of urinary/bladder and sexual symptoms associated with such condition.…”
Section: Discussionmentioning
confidence: 95%